2020
DOI: 10.1016/j.ces.2020.115640
|View full text |Cite
|
Sign up to set email alerts
|

Implications of hydrodynamics on the design of pulsed sieve-plate extraction columns: A one-fluid multiphase CFD model using the volume of fluid method

Abstract: This is a repository copy of Implications of hydrodynamics on the design of pulsed sieveplate extraction columns: A one-fluid multiphase CFD model using the volume of fluid method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…This highlights the problems encountered when trying to apply modelling paradigms suitable for "idealized" flow configurations, such as the fully dispersed and the large-scale/segregated interface assumptions, to "real-life" multiscale complex flows. This has been demonstrated in the context of liquid-liquid extraction in the recent LES/VoF simulation of a Pulsed Sieve-plate Extraction Column reported in [12]. It has been observed that an extremely fine mesh, associated with an unfeasible computational cost, would be required to resolve the single droplets within the system following an interface-resolving approach; including the effects of the presence of these droplets, on the other hand, is key for the correct representation of the hydrodynamic behaviour and of the mass transfer within the system.…”
Section: Introductionmentioning
confidence: 74%
“…This highlights the problems encountered when trying to apply modelling paradigms suitable for "idealized" flow configurations, such as the fully dispersed and the large-scale/segregated interface assumptions, to "real-life" multiscale complex flows. This has been demonstrated in the context of liquid-liquid extraction in the recent LES/VoF simulation of a Pulsed Sieve-plate Extraction Column reported in [12]. It has been observed that an extremely fine mesh, associated with an unfeasible computational cost, would be required to resolve the single droplets within the system following an interface-resolving approach; including the effects of the presence of these droplets, on the other hand, is key for the correct representation of the hydrodynamic behaviour and of the mass transfer within the system.…”
Section: Introductionmentioning
confidence: 74%
“…The d* is too small to capture microscale details but too large to contain a droplet cluster. Theobald et al 15 investigated a pulsed sieve‐plate extraction column using a volume of fluid and large eddy simulation (VOF‐LES) coupled model. The fine grid predicted the droplet dispersion in the region containing the sieve plates.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsing action in these columns is implemented pneumatically. Their simple design, lower space requirement, higher throughput, and no moving parts make them more appealing. , Numerous investigations have been conducted on laboratory/bench and pilot-scale PSPCs to study the effect of various operating and geometrical parameters on the hydrodynamic and mass transfer performance of these columns. However, most of the studies reported on PSPC culminated in different empirical correlations causing indecision amongst design engineers about the appropriateness of the correlation. This problem is made more acute because, in the majority of the cases, the column is considered as a blackbox and the measured column performance, like holdup, drop diameter, axial dispersion, and mass transfer coefficient, is correlated to input (known) conditions. There has not been much emphasis on understanding the underlying flow patterns, which essentially dictate the column performance.…”
Section: Introductionmentioning
confidence: 99%
“…Their simple design, lower space requirement, higher throughput, and no moving parts make them more appealing. 1,2 Numerous investigations have been conducted on laboratory/bench and pilot-scale PSPCs to study the effect of various operating and geometrical parameters on the hydrodynamic and mass transfer performance of these columns. 3−11 However, most of the studies reported on PSPC culminated in different empirical correlations causing indecision amongst design engineers about the appropriateness of the correlation.…”
Section: Introductionmentioning
confidence: 99%